2020
DOI: 10.1111/tpj.15023
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture to cause dynamic change in tiller and panicle numbers revealed by genome‐wide association study and transcriptome profile in rice

Abstract: Panicle number (PN) is one of the three yield components in rice. As one of the most unstable traits, the dynamic change in tiller number (DCTN) may determine the final PN. However, the genetic basis of DCTN and its relationship with PN remain unclear. Here, 377 deeply re-sequenced rice accessions were used to perform genome-wide association studies (GWAS) for tiller/PN. It was found that the DCTN pattern rather than maximum tiller number or effective tiller ratio is the determinant factor of high PN. The DCTN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…S8B ), consistent with previous studies [ 43–45 ]. We found that PSR-1 significantly decreased the expression levels of the positive growth regulator OsGPAT1 [ 46 ] and significantly increased the expression levels of the negative growth regulator OsSAUR27 [ 47 ] compared to the uninoculated mock and E. coli treatment when rice was submerged for 4 days ( Fig. 4C ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S8B ), consistent with previous studies [ 43–45 ]. We found that PSR-1 significantly decreased the expression levels of the positive growth regulator OsGPAT1 [ 46 ] and significantly increased the expression levels of the negative growth regulator OsSAUR27 [ 47 ] compared to the uninoculated mock and E. coli treatment when rice was submerged for 4 days ( Fig. 4C ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A panel of 2154 cultivated and 221 wild rice varieties was used to construct a phylogenetic tree of the TN1 gene sequence according to previously described methods (Li et al, 2021). A minimum spanning tree of haplotypes using the same data was calculated following a previously described method (Guo et al, 2020).…”
Section: Evolutionary Analysis Of Tn1 and Its Genome Sequencementioning
confidence: 99%
“…It was recently found that tiller‐regulating genes usually showed high expression in the root at 24:00. Based on this expression pattern and a genome‐wide association study (GWAS), a small auxin‐UP RNA gene, OsSAUR27 , was identified in natural populations and has been proven to affect tiller number and plant architecture (Ma et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 In addition, the number of genes controlling the panicle number and size that have been cloned is also increasing, and examples are IPA1, 12 PANDA, 13 and OsSAUR27. 14 Studies on rice quality improvement, especially ECQ and appearance quality, have been focused on the enzymes involved in the biosynthesis of amylose and amylopectin, the constituent starch polymers in seeds. Nevertheless, most of these cloned genes can only improve limited aspects of the target traits, without positive contributions and even causing possible negative effects on other nontarget traits.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, scientists usually seek to clone novel target genes involved in controlling the panicle number, grain number, and grain weight and size, using them to generate rice varieties with more panicles and grains, larger and heavier grains, and finally increased rice yield. In general, the majority of these cloned genes in rice are related to sink organs. It is impressive that more than 80 grain size-related genes have been cloned, , including GS3 , DEP1 , GW2 , and qGL3 / OsPPKL1 . , In addition, the number of genes controlling the panicle number and size that have been cloned is also increasing, and examples are IPA1 , PANDA , and OsSAUR27 . Studies on rice quality improvement, especially ECQ and appearance quality, have been focused on the enzymes involved in the biosynthesis of amylose and amylopectin, the constituent starch polymers in seeds.…”
Section: Introductionmentioning
confidence: 99%